Impact of an Educational Training Program on the Knowledge, Attitude, and Perceived Barriers of Community Pharmacists Towards Obesity and Overweight Management in Malaysia - Rohit Kumar Verma; Rohit Kumar Verma; Wei Wen Chong; Nur Akmar Taha; Thomas Paraidathathu (Frontiers Media S.A., 2021)
Objective: To evaluate the impact of an educational training program on the knowledge, attitude and perceived barriers of community pharmacists (CPs) towards obesity and overweight management.Methods: This interventional study, which consisted of an educational training program, was conducted on a single cohort of Malaysian CPs. Thirty CPs attended the educational training program. The educational training program was delivered through didactic lectures, case studies and small group discussions, and consisted of various sessions covering different topics related to weight management. A validated questionnaire was used to assess the impact of the intervention on the CPs' knowledge, attitude, and perceived barriers.Results: The overall mean knowledge score increased both immediately after (14.93 ± 1.62) and 30 days following the intervention (17.04 ± 2.51), and the increment was statistically significant 30 days following the intervention (p = 0.001) compared to both pre-intervention and immediate-post intervention stages. After the intervention, the participants had a more positive attitude towards the provision of weight management service (WMS) in community pharmacies. They had significantly stronger perceptions about the importance of their role to manage overweight and obesity and their professional competence to treat obese patients. In addition, the barrier of not having space in pharmacy to perform proper counselling for weight management and the barrier of not having training sessions in the area of obesity management were perceived to be significantly less important post-intervention.Conclusion: This study showed the potential positive impact of an educational training program on CPs knowledge, attitudes and perceived barriers towards WMS.